The money class : how to stand in your truth and create the future you deserve - Orman, Suze (United States : Spiegel & Grau, 2012)
Suze Orman, the woman millions of Americans have turned to for financial advice, delivers a master class on personal finance and teaches her readers that the'New American Dream' is not the things they accumulate, but the confidence that comes from knowing that which they've worked so hard for cannot be taken away from them.
How to enter the classroom -- Introduction --Class I. The new American dream -- Making change -- The dreams of tomorrow reside in today's choices -- The money class curriculum -- Class 2. Stand in your truth -- Finding your truth : a personal financial accounting -- Living truthfully : how to stand tall in your reality -- Focus on what is real today ... and what you will need tomorrow -- Live below your means but within your needs -- The pleasure of saving is equal to the pleasure of spending -- Define yourself by who you are, not what you have -- The foundation of all truthful living : the power of cash -- Debit card rules -- The'life happens' fund -- Credit Unions : a great place to save -- Safety first with your savings -- Saving for big-ticket items -- The truth will indeed set you free -- Class 3. Family -- How to build honest family relations -- Opening the lines of communication --How to raise young children to stand in the truth --Your priceless legacy -- Set the right tone -- Imparting good values when it comes to money --Money lessons for children -- Money lessons for tweens and teens -- Money lessons for teenagers heading to college -- How to handle money gifts and savings -- The three-option approach -- How to create a financially honest college strategy -- Who should save for college -- The best way to save for college : 529 Plans -- UGMA /UTMA -- Coverdell Accounts -- How to invest your 529 Plan -- The college talk every parent must have with a hight school freshman -- Borrowing rules for college loans -- The risks of private loans for college -- Stafford Loans -- PLUS Loans -- How to choose the right school -- How to help adult children facing financial challenges -- How to handle student loans that are in default -- How and when to help independent children who are in financial trouble -- The conversation every adult child should have with his or her parents -- Building family financial security under one roof --Updating legal documents --When a parent remarries -- Advise for grandparents : how to build a lasting legacy -- Follow the parents' lead -- Pay it forward -- Give experiences, not things -- Class 4. Home -- The truth about home values --A decade of extremes -- A home is a savings account, not a hot stock -- Financing is cheap, but not easy -- When it makes sense to rent -- The math of rent vs. buy -- Advice for owners who now want to rent -- The new rules of buying a home --Set a budget that satisfies your needs -- Know your income limits -- Aim to make a 20% down payment -- A special note about FHA-insured loans -- Special rules for buying condos and co-ops -- Where to come up with the down payment -- Opt for a 30-year fixed-rate mortgage -- Understand the risk of distressed property -- What to do if you are underwater -- If you are underwater and cannot afford your mortgage -- Loan modification -- Short sale -- Foreclosure -- If you are underwater but you can afford the mortgage -- How to reduce mortgage costs -- When it makes sens to pay off a loan ahead of schedule -- The new realities of refinancing --Refinancing rules -- Lower your mortgage costs without a refinance -- The dangers of home equity lines of credit -- Dangers of rising interest rates and falling behind on payments -- Home equity loans --Reverse mortgages -- Investing in real estate --What you need to know before you buy investment property -- What to do with an investment property that is underwater. Class 5. Career -- Advice for the employed -- Build your plan-for-the-worst fund --Live below today's means -- Grab your full retirement bonus -- Make your case for a raise and promotion through your work -- Change your attitude before you change your job -- Advice for the unemployed -- Cut your spending immediately --Do not dip into your retirement savings -- Make sure your credit profile remains strong -- Do not go back to school to avoid a hard job market --Get to work as fast as possible -- How to deal with a steep pay cut -- Special note for stay-at-home Moms --Starting (and running) your own business -- Can you afford it? -- Where to get the money to start your own business -- Micro lending -- When to expand -- When to close -- Standing in your truth in business -- Closing down a business responsible --Retirement classes -- Class 6. Retirement planning : getting going in your 20s and 30s -- Time is your greatest asset -- Savings -- Retirement accounts explained -- Retirement plans offered by employers -- Retirement plan withdrawal rules -- Non workplace retirement accounts -- Nondeductible IRAs -- Roth IRAs -- Retirement plans for the self-employed -- How much you need to save for retirement -- The retirement formula -- the best 401(k) and IRA strategy -- A word on vesting -- Where to open an IRA account -- Investing your retirement money -- Ups and downs of the stock market -- Dollar cost averaging -- How much to invest in stocks -- Choosing the best options within your 401(k) -- How to build the best 401(k) investment portfolio -- Exchange traded funds --Bond investments -- Retirement planning mistakes to avoid -- What to do with your 401(k) when you leave a job -- Class 7. Retirement planning : fine-tuning it in your 40s and 50s -- Deciding when it makes sense to pay off your mortgage -- Have a realistic plan for working until age 66-67 -- Your work-longer game plan -- Delay your Social Security benefit -- Estimate your retirement income -- Social Security benefits -- Retirement accounts -- Pensions -- Lump sum vs. annuity -- Saving more, and investing strategies in your 50s -- Best investments outside your 401(k) -- Bond investments -- No target funds allowed -- Plan for long-term care costs --Financial case for LTC insurance -- Health insurance, Medicare, and Medicaid -- LTC basics --Class 8. Living in retirement -- Home finances : stand in the truth of what is affordable for you.
'Revised & updated' --- Cover.
2012 Spiegel & Grau Trade Paperback Edition.
Koleksi sumbangan Tun Ahmad Sarji Abdul Hamid.
Keywords: Finance, Personal -- United States; Wealth -- United States